Justifying Water Sensitive Development: Science Informing Policy and Practice - van Roon, Marjorie R. (European Journal of Sustainable Development, 2017)
This New Zealand research focuses on providing evidence that a specified residential land use layout plus „at source? stormwater management results in higher aquatic ecosystem health. The evidence provides justification for changes in statutory plans, policies and practice rules that direct urban development. The surveyed sites are within river basins clustered by similar residential land use density. Each cluster includes one river basin with conventional urban form and drainage. Other comparative basins in the cluster typify a „water sensitive? urban form and infrastructure. An index of biotic integrity (indicating river health) is determined for each waterway at annual intervals over years. Current plan requirements, policies and practice guidelines for urban development are critiqued in relation to survey results. The cumulative influence of defined residential river basin characteristics (drivers) are related to the holistic biotic indices. Combined drivers determine the cumulative aquatic health outcome. Research methods typically don?t target the effects of a single driver. Policy, plan and practice requirements need to guide urban design and construction to incorporate the elements of urban form that are together necessary for aquatic health. This will ensure an order of magnitude improvement in the functionality and recreational appeal of streams, wetlands, lakes and recipient harbours. Keywords: Water sensitive urban design; biotic integrity; urban planning